Phenomenological Study of Nginum Brem Reket Bontok: The Sasak Bayan Traditional Ritual in Bayan Beleq Village, North Lombok Regency, West Nusa Tenggara - Dirga, Dewa Made; Zaki, Lalu Ahmad (Media Wisata, 2024)
This research explores the phenomenon of "Nginum Brem Reket Bontok" as part of the indigenous tradition of the Sasak Bayan community in Bayan Beleq Village, North Lombok Regency, West Nusa Tenggara. The approach utilized is qualitative methodology employing phenomenological principles, particularly Husserlian Phenomenology. This study aims to describe and deeply understand the life experiences of the Sasak Bayan community in consuming Brem, a traditional beverage imbued with strong symbolic and religious values within their culture. The research employed data collection techniques including observation, in-depth interviews, and data-based deduction. The analyzed data reveals that the tradition of "Nginum Brem" not only involves beverage consumption but also reflects the Sasak Bayan community's cultural richness, beliefs, and social practices. The findings of this study are expected to provide deeper insights into how this local tradition is integrated within social and religious contexts, as well as its implications for sustainable cultural tourism in West Nusa Tenggara. This research contributes significantly to developing knowledge regarding the interaction between local culture and religious practices within the broader context of cultural tourism in Indonesia, particularly in West Nusa Tenggara Province.